Service Functions of Tax Regulation for the Purposes of State Development in the Globalized Environment - ZEYNALOVA, Zivar Z. (Journal of Advanced Research in Law and Economics, 2019)
The tax regulation is an important element of creation and distribution of the qualitative budgeting of a city or a state. Tax regulation allows evenly distributing the existing resources and thus ensuring the gradual development of a state. The task of legal regulation is to ensure the equal distribution of the tax burden and the formation of the integral perception on the part of the population of the suggested regulatory measures. The search of the equilibrium and the formation of the system of legal regulation based on the analysis of the best practices of the European states forms the relevance of the study. The novelty of the study is defined by the fact that to a greater extent, the formation of the model of sufficient tax regulation is possible if it is a targeted indicator of the social and economic development of the state. The authors of the paper except for analyzing the taxation systems of the majority of the EU states also define the way necessary for the implementation of the legislation elements in the states of the post-Soviet territory. According to the authors, it will allow to a greater extent define how the tax incomes should be distributed. The practical significance of the study is defined by the fact that at the implementation of the paper’s conclusions one may precisely define that different distribution of the funds will allow to a greater extent feasibly reforming the tax legislation in the developing countries.